Seeking equity for women in journalism and mass communication education : a 30-year update - Rush, Ramona R. (LEA's communication series., 2004)
Starting from their 1972 study of women's status in journalism and mass communication education, editors Ramona R. Rush, Carol E. Oukrop, and Pamela J. Creedon examine women's struggles for equity since the early 1970s and identify what issues still lie ahead.